The Role of Syariah Penal Code (Cap. 275) in Determining Criminal Responsibility for Minors in Brunei Darussalam - Ahmad Masum; Yusuf Ibrahim Arowosaiye; Hjh Hanan Hj Awg Abd Aziz; Rajali Aji (PT. Islamic Research Publiser, 2026)
This article examines the construction of criminal responsibility for minors under the Syariah Penal Code (Cap. 275) within Brunei Darussalam’s dual legal system, where civil and Syariah laws operate concurrently for Muslim citizens. The study aims to analyze how the Syariah framework conceptualizes juvenile accountability and to assess its compatibility with international child justice standards. Employing a doctrinal and comparative legal approach, the research systematically reviews statutory provisions in the Syariah Penal Code (Cap. 275), contrasts them with the Penal Code (Cap. 22), and evaluates their alignment with Article 40 of the United Nations Convention on the Rights of the Child (UNCRC). The findings reveal that, unlike the civil legal system, which primarily relies on chronological age thresholds, the Syariah Penal Code adopts a capacity-based model grounded in the concept of taklif. Criminal responsibility is determined by indicators such as discernment (tamyiz), puberty (bulugh), and ʿaql (mental capacity), enabling a more individualized assessment of culpability. This framework effectively excludes minors from the full application of hudud and qisas punishments, instead emphasizing mitigated or discretionary sanctions. However, the absence of a clearly defined minimum age of criminal responsibility poses significant challenges, including potential legal uncertainty, inconsistent judicial interpretation, and tension with international norms that prioritize clear age limits, diversion mechanisms, and detention as a last resort. Academically, this research contributes to the development of comparative Islamic criminal law by offering a nuanced analytical framework that bridges classical doctrines of taklif with contemporary human rights discourse. It enriches the scholarship on dual legal systems by demonstrating how normative tensions between religious and international legal standards can be constructively reconciled.